MECHANICS OF THREADED FASTENERS AND BOLTED JOINTS FOR ENGINEERING AND DESIGN - FUKUOKA, TOSHIMICHI (ELSEVIER, 2023)
The Mechanics of Threaded Fasteners and Bolted Joints outlines how threaded fasteners and bolted joints fail, how these failures can be remedied, and ultimately how to avoid them altogether through tightening methods, material strength, and avoiding loosening. The book demonstrates how to select the appropriate tightening method and determine the optimal tightening procedure for varying nominal diameters. Using the finite element method, it discusses characteristics of stress concentration and fatigue strength and covers bolt force variation due to elastic interaction. The separation of the plate interface via increased external force as the primary cause of fatigue failure in threaded fasteners is discussed, with effective countermeasures provided. Empirical equations of thermal contact coefficient and apparent thermal contact coefficient in simple form are included as well.
Keywords: Bolted joints.; Fasteners.; Screw-threads.; elektronické knihy; electronic books